Limitations of the kinematic approximation in neutron reflectivity measurements for the analysis of bilayers. Issue 6 (25th October 2018) - Droulias, Sotirios A.; Pálsson, Gunnar K.; Hjörvarsson, Björgvin; Wolff, Max
Abstract : Neutron reflectivity on metallic superlattices is used to measure the volume expansion induced by deuterium content. The differences between treating the data with simple Gaussian fits and full reflectivity fits using Parratt's recursive method are shown and an explanation is proposed. Abstract : The limitations of a phenomenological fitting approach compared to simulations of the optical model including reflection and refraction at all interfaces are demonstrated using the example of hydrogen loading in ultra‐thin vanadium layers. Fe/V superlattices are loaded with deuterium and the lattice expansion and deuterium concentration are extracted from neutron reflectivity data. A noticeable difference is found between the extraction of concentrations and bilayer thicknesses directly from the superlattice peaks and fits of the density profile using the Parratt formalism. The results underline the importance of carefully considering the limitations of phenomenological approaches, in order to obtain robust results. The limitations of the kinematic approximation for the analysis are discussed in detail.